2008
DOI: 10.1007/s00702-008-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interactions between cannabinoid compounds and diazepam in electroshock-induced seizure model in mice

Abstract: Several studies have shown that cannabinoids have anticonvulsant properties that are mediated through activation of the cannabinoid CB1 receptors. In addition, endogenous cannabinoid compounds (endocannabinoids) regulate synaptic transmission and dampen seizure activity via activation of the same receptors. The aim of this study was to evaluate the possible interactions between antiepileptic effects of cannabinoid compounds and diazepam using electroshock-induced model of seizure in mice. Electroconvulsions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…This finding is consistent with other studies demonstrating WIN55212-2 produced an anticonvulsant effect in both in vivo [17] and in vitro [2] models of seizure. Moreover, these data complement our previous study showed WIN55212-2 produced protective effect in electroshock-induced seizure in mice [18]. Activation of cannabinoid CB1 receptor reduces the release of the excitatory neurotransmitter glutamate in CNS neurons [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding is consistent with other studies demonstrating WIN55212-2 produced an anticonvulsant effect in both in vivo [17] and in vitro [2] models of seizure. Moreover, these data complement our previous study showed WIN55212-2 produced protective effect in electroshock-induced seizure in mice [18]. Activation of cannabinoid CB1 receptor reduces the release of the excitatory neurotransmitter glutamate in CNS neurons [19].…”
Section: Discussionsupporting
confidence: 84%
“…Pre-treatment of rats with FAAH inhibitor URB597 did not produce significant change in the latency of seizure occurrence in PTZ-induced model of seizure, although previous work in this laboratory revealed a protective effect of URB597 against electroshock-induced seizure [18]. This could be in part due to the differences in the mechanism of seizure induction in these two models which affect different ion channels and receptors.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Accumulating experimental evidence indicates that one of the synthetic cannabimimetic compounds [i.e., WIN 55,212-2 mesylate (WIN)—a highly potent non-selective cannabinoid CB 1 and CB 2 receptor agonist] potentiated the anticonvulsant activity of some classical antiepileptic drugs (i.e., diazepam, carbamazepine, phenytoin, phenobarbital and valproate) and second-generation antiepileptic drugs (i.e., lamotrigine, pregabalin and topiramate) in the mouse maximal electroshock-induced tonic seizure (MES) model (Luszczki et al 2011b, 2013; Naderi et al 2008). WIN also enhanced the anticonvulsant activity of ethosuximide, phenobarbital and valproate in the mouse pentylenetetrazole-induced clonic seizure (PTZ) model (Luszczki et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…WIN55212, a CB 1 receptor agonist with effects similar to THC, was given at low doses in tandem with low doses of ethosuximide (Luszczki et al, 2011a), phenobarbital (Luszczki et al, 2011a(Luszczki et al, , 2011b, valproate (Luszczki et al, 2011a(Luszczki et al, , 2011b, carbamazepine (Luszczki et al, 2011b), phenytoin (Luszczki et al, 2011b), and diazepam (Naderi et al, 2008) to produce enhanced anticonvulsant effects in mice. In a similar fashion, the synthetic CB 1 receptor agonist arachidonyl-29-chloroethylamide was tested with low dose injections of naltrexone (Bahremand et al, 2008) and phenobarbital (Luszczki et al, 2010) to produce an additive anticonvulsant effect in mice.…”
mentioning
confidence: 99%